(untitled) (Pedagogy of Higher and Secondary Education, 2011)
Theoretical survey and analysis of scientific literature about professional thought developing in up-to-date psychology, psychological ad pedagogical fundamentals of mining trade schools students thinking are discussed and characterized in the article